Stabilisation of marine clay using polyurethane - Saleh, Samaila (2021)
The recent need driven by global population growth to build more infrastructures is forcing authorities to build on any soil type available within their vicinity, including weak soils like marine clay (MC). However, due to its poor engineering properties, MC is not suitable for construction purposes. Given this fact, many ground improvement techniques are being employed to improve the properties of MC and to reduce the potential damages caused by it. Although researchers have done a lot to improve the properties of MC using different materials and methods, attention has not been given to the application of polyurethane (PU) to stabilise MC. Therefore, this research focusing on the application of PU for the stabilisation of MC. The MC was characterised by testing its index and engineering properties as well as the geochemistry and microstructure. Correspondingly, PU was characterised by testing its rheological and mechanical properties alongside the microstructural analyses. The effectiveness of PU as a stabiliser was evaluated using unconfined compression tests, consolidated undrained (CU) triaxial tests and one-dimensional consolidation tests to determine the strength and stiffness. Furthermore, x-ray diffraction (XRD) analysis, field emission scanning electron microscopy (FESEM) and energy dispersive spectroscopy (EDX) were used to discern the roots of improvement in the strength of the MC that was stabilised with PU. PU properties were also improved using reinforcing fillers. Additionally, the bearing capacity of the MC before and after treatment with PU piles was evaluated using physical and numerical models. Finally, the potential for ground contamination resulting from the application of PU to stabilise MC was investigated using toxicity characteristic leaching procedures (TCLP). The results obtained show that PU improved the shear strength and the stiffness parameters of the MC. Neutralising the acidity of MC with NaOH nearly doubled the strength and stiffness of the PU-stabilised MC. The UCS of MC that was treated with PU and NaOH improved significantly. Likewise, the secant stiffness for the CU triaxial test and tangent stiffness for the primary oedometer loading, show improvement compared to the untreated MC sample. Results of the microstructure analyses revealed that no new compounds were formed during the stabilisation of the MC with PU. The improvement in MC strength was due to the densification and coating of MC particles with PU foam. PU improved with SiO2 have superior strength, stiffness and crystallinity compared to the normal PU due to the cross-linking properties of the of SiO2 particles in the chain of PU. The results from the numerical model showed that the bearing capacity of MC that was stabilised with PU piles increases with increase in an improvement area ratio and with a length over height ratio compared to the untreated MC. The TCLP results revealed that the quantity of heavy metals present in PU is far below the regulatory limits. The results further confirmed that PU is odourless, non-corrosive and both non-cyanide and non-sulphide bearing. However, PU is capable of igniting. Overall, the potential application of PU for ground improvement is promising due to its environmental friendliness and high strength.